2003
DOI: 10.1093/heapro/dag021
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control and gender in Southeast Asia. Part I: Malaysia and the Philippines

Abstract: In the World Health Organization's Western Pacific Region, being born male is the single greatest risk marker for tobacco use. While the literature demonstrates that risks associated with tobacco use may vary according to sex, gender refers to the socially determined roles and responsibilities of men and women, who initiate, continue and quit using tobacco for complex and often different reasons. Cigarette advertising frequently appeals to gender roles. Yet tobacco control policy tends to be gender-blind. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 13 publications
5
47
0
3
Order By: Relevance
“…13,14,20 In addition, earlier studies have shown that the tobacco industry intentionally targeted women by focusing on female-identified needs, preferences, and positive images of smoking, [21][22][23] although there are no conclusive studies of how the tobacco industry targets women and teenage consumers in Taiwan. More work should be done to monitor and decrease the impact of the trade liberalization and cigarette marketing on smoking in these minority groups.…”
Section: Logistic Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,20 In addition, earlier studies have shown that the tobacco industry intentionally targeted women by focusing on female-identified needs, preferences, and positive images of smoking, [21][22][23] although there are no conclusive studies of how the tobacco industry targets women and teenage consumers in Taiwan. More work should be done to monitor and decrease the impact of the trade liberalization and cigarette marketing on smoking in these minority groups.…”
Section: Logistic Regressionmentioning
confidence: 99%
“…8,10,11,13,14,20 Traditional values and normative gender expectations may be becoming less of a protective factor against smoking in women in Asia. Therefore, it is crucial to gain a deeper understanding of the normative gender roles and social values of modern Asian women and identify the effects of sociocultural influences on cigarette diffusion and behaviors.…”
Section: Logistic Regressionmentioning
confidence: 99%
“…The increased smoking among women could reflect either the shift towards modernization and emancipation of women in this region or the specific targeting of women by the tobacco indus try as a huge untapped market for its products, or both (Mackay & Amos, 2003;Morrow & Barraclough, 2003). A recent study by Parkinson et al (2009), using adolescents' data from the first wave of the International Tobacco Control Southeast Asia (ITCSEA) survey, showed that female adolescents were less likely to hold positive aesthetic and social acceptability beliefs about smoking compared with their male counterparts, that Thai adolescents were more likely to endorse these beliefs, and that these beliefs were strongly predictive of smoking susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…We should not ignore the role of gender differences in our tobacco policy. We need to be concern and refute the acceptance of male smoking as being born male is found to be the single major risk factor for tobacco use (Morrow et al, 2003). The major strengths of our study include a prospective design that follows an adolescent cohort over a period of one year.…”
mentioning
confidence: 99%